Emerging Trends in Nanotechnology: Aerogel-Based Materials for Biomedical Applications - Noremylia Mohd Bakhori; Zarini Ismail; Mohamad Zaki Hassan; Rozzeta Dolah (Nanomaterials, 2023)
At present, aerogel is one of the most interesting materials globally. The network of aerogel consists of pores with nanometer widths, which leads to a variety of functional properties and broad applications. Aerogel is categorized as inorganic, organic, carbon, and biopolymers, and can be modified by the addition of advanced materials and nanofillers. Herein, this review critically discusses the basic preparation of aerogel from the sol–gel reaction with derivation and modification of a standard method to produce various aerogels for diverse functionalities. In addition, the biocompatibility of various types of aerogels were elaborated. Then, biomedical applications of aerogel were focused on this review as a drug delivery carrier, wound healing agent, antioxidant, anti-toxicity, bone regenerative, cartilage tissue activities and in dental fields. The clinical status of aerogel in the biomedical sector is shown to be similarly far from adequate. Moreover, due to their remarkable properties, aerogels are found to be preferably used as tissue scaffolds and drug delivery systems. The advanced studies in areas including self-healing, additive manufacturing (AM) technology, toxicity, and fluorescent-based aerogel are crucially important and are further addressed.